Patient perceptions and predictors of intention to use telehealth for follow-up care: a mixed methods study among adults living with HIV in Kampala, Uganda - Charles Peter Osingada; Barbara J. McMorris; Mary Fran Tracy; Noeline Nakasujja; Tom Denis Ngabirano; Carolyn M. Porta (BMC Health Services Research)
Abstract Background The human immunodeficiency virus (HIV) remains a significant global public health challenge. Despite progress in addressing the pandemic, people living with HIV continue to report challenges in accessing HIV testing, care, and treatment services. Telehealth presents a promising solution to some of these barriers. However, its potential remains unrealized, particularly in low- and middle-income settings, partly due to insufficient supporting evidence. Methods Our mixed methods study investigated patient perceptions and predictors of intention to use telehealth for follow-up HIV care in Uganda. Quantitative data were collected from 266 participants using a questionnaire, followed by one-on-one interviews with 12 people living with HIV. Quantitative analysis involved Chi-square tests, t-tests, and binary logistic regression, while qualitative data were analyzed using conventional content analysis. Results Our findings show that the intention to use telehealth was significantly associated with effort expectancy (aOR 1.26, CI 1.13–1.41), facilitating conditions (aOR 1.44, CI 1.19–1.73), estimated monthly income (aOR 2.94, CI 1.05–8.23; aOR 7.29, CI 1.12–47.49), and antiretroviral medication adherence (aOR 1.93, CI 1.12–3.33). Qualitative insights underscore the importance of digital literacy and availability of support services to enhance the utilization of telehealth. While performance expectation and stigma score did not significantly predict intention to use telehealth, participants perceived telehealth to be beneficial in combating stigma and improving access to HIV care services. Conclusions To optimize the utilization of telehealth, we recommend measures aimed at addressing economic disparities and enhancing digital literacy among people living with HIV. Future research should explore the effectiveness of economic empowerment programs in promoting telehealth use and investigate the impact of telehealth on HIV care models, stigma reduction, and linkage and retention in HIV care.